2016
DOI: 10.1073/pnas.1608125113
|View full text |Cite
|
Sign up to set email alerts
|

Structural definition of the lysine swing in Arabidopsis thaliana PDX1: Intermediate channeling facilitating vitamin B 6 biosynthesis

Abstract: Vitamin B 6 is indispensible for all organisms, notably as the coenzyme form pyridoxal 5′-phosphate. Plants make the compound de novo using a relatively simple pathway comprising pyridoxine synthase (PDX1) and pyridoxine glutaminase (PDX2). PDX1 is remarkable given its multifaceted synthetic ability to carry out isomerization, imine formation, ammonia addition, aldol-type condensation, cyclization, and aromatization, all in the absence of coenzymes or recruitment of specialized domains. Two active sites (P1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 53 publications
3
20
0
Order By: Relevance
“…The PDX1/PDX2 protein pair, which forms a PLP synthase, is widely distributed among archaea, bacteria, fungi, protists, and plants, and the corresponding complexes have been characterized in a variety of pro- and eukaryotes, including Geobacillus stearothermophilus (PdxS/PdxT) [ 48 , 49 ], B. subtilis (Pdx1/Pdx2 or PdxS/PdxT) [ 50 , 51 ], Thermotoga maritima (YaaD/YaaE) [ 52 ], S. cerevisiae [ 52 , 53 ], A. thaliana [ 54 ], and Plasmodium falciparum [ 55 ].…”
Section: Complex Organization Of Plp Synthasesmentioning
confidence: 99%
See 2 more Smart Citations
“…The PDX1/PDX2 protein pair, which forms a PLP synthase, is widely distributed among archaea, bacteria, fungi, protists, and plants, and the corresponding complexes have been characterized in a variety of pro- and eukaryotes, including Geobacillus stearothermophilus (PdxS/PdxT) [ 48 , 49 ], B. subtilis (Pdx1/Pdx2 or PdxS/PdxT) [ 50 , 51 ], Thermotoga maritima (YaaD/YaaE) [ 52 ], S. cerevisiae [ 52 , 53 ], A. thaliana [ 54 ], and Plasmodium falciparum [ 55 ].…”
Section: Complex Organization Of Plp Synthasesmentioning
confidence: 99%
“…In plants, two recent studies have shown that PLP synthases contain a lysine swing or lysine relay mechanism that allows intermediate channeling of the substrate in the process of vitB 6 biosynthesis [ 54 , 56 ]. Essentially, the lysine residues anchor the substrate to the PLP synthase and facilitate transfer of the substrate between the two active sites efficiently without extra domains or coenzymes [ 54 ]. These two sites are present in PDX1 proteins and are designated as P1 and P2 [ 56 ].…”
Section: Complex Organization Of Plp Synthasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several PLP synthase enzymes from bacteria, archaea, yeast and plants, have been characterized biochemically with and without the associated glutaminase (Dong et al 2004; Burns et al 2005; Raschle et al 2005; Gengenbacher et al 2006; Strohmeier et al 2006; Zein et al 2006; Raschle et al 2007; Hanes et al 2008; Neuwirth et al 2009; Raschle et al 2009; Moccand et al 2011; Robinson et al 2016; Rodrigues et al 2017). A variety of names have been used for the genes encoding PLP synthase and glutaminase enzymes, e.g.…”
mentioning
confidence: 99%
“…183 PDX1.3 implements an extremely efficient lysine relay mechanism where all catalytic action 184 happens within a single domain (catalytic sites P1 and P2). Two key residues K98 and K166 trap the 185 substrates, covalently tether the intermediates and then shuttle the product out5,20 . We compared the 186 obtained Cryo-EM structure of inactive PDX1.2 with several crystallographic structures of PDX1.3 187 available at different stages of such action: precursor binding stage PDX1.3-R5P (PDB:5lns), 188 intermediate stage PDX1.3-I 320 (PDB:5lnu), post-intermediate PDX1.3-I 320 -G3P (PDB:5lnw) and final 189 product stage where PLP is still covalently bound to K166 (PDB:5lnr) (Fig.3a).…”
mentioning
confidence: 99%